1990
DOI: 10.1161/01.cir.82.6.2011
|View full text |Cite
|
Sign up to set email alerts
|

Airway hyperresponsiveness in patients with microvascular angina. Evidence for a diffuse disorder of smooth muscle responsiveness.

Abstract: Anginal chest pain in patients with angiographically normal coronary arteries may be caused by a limited coronary flow response to stress because of abnormal function of the coronary microcirculation (microvascular angina). Studies of forearm arterial function suggested that patients with microvascular angina may have a diffuse disorder of smooth muscle tone. Because dyspnea is common in these patients and seems disproportionate to the severity of myocardial ischemia, we studied air flow (forced expiratory vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Furthermore, ST segment changes during stress testing have historically been classified as false positives when they coincide with normal angiographic vasculature, and their concurrent chest pain has sometimes been classified as of non-cardiac origin including psychosomatic disorders and altered pain perception [181][182][183][184][185][186] . Studies by this group also revealed systemic smooth muscle disorders in the esophagus, bronchus, and systemic arteries [195][196][197] in this unique patient population indicating the possible involvement of a diffuse smooth muscle disorder. [175] in which they described a group of women who complained of chest pain with ECG changes during exercise testing and yet had angiographically normal coronary arteries.…”
Section: Impact Of Microvascular Disease On the Heartmentioning
confidence: 56%
“…Furthermore, ST segment changes during stress testing have historically been classified as false positives when they coincide with normal angiographic vasculature, and their concurrent chest pain has sometimes been classified as of non-cardiac origin including psychosomatic disorders and altered pain perception [181][182][183][184][185][186] . Studies by this group also revealed systemic smooth muscle disorders in the esophagus, bronchus, and systemic arteries [195][196][197] in this unique patient population indicating the possible involvement of a diffuse smooth muscle disorder. [175] in which they described a group of women who complained of chest pain with ECG changes during exercise testing and yet had angiographically normal coronary arteries.…”
Section: Impact Of Microvascular Disease On the Heartmentioning
confidence: 56%
“…These same authors also demonstrated that some patients with microvascular angina may have a generalised disorder of vascular and nonvascular smooth muscle function 13. Finally, some authors suggested a possible link between hyperinsulinaemia and microvascular dysfunction 14…”
Section: Syndrome Xmentioning
confidence: 88%
“…[37][38][39] The differences between these 2 agents regarding their receptor distribution and ability to induce endothelium-derived vasodilation or constriction of arterial smooth muscles may be involved in the different results obtained in the present study and those of Saitoh et al 24 Because ACh and MCh challenges have been reported to yield similar high levels of sensitivity and specificity for revealing airway hyperresponsiveness, we consider that the differences between these 2 agents did not affect our results. 40 Influences of age, 41 sex, smoking habits, 42 allergic factors, [43][44][45] left ventricular ejection fraction 46 and microvascular angina 47 on airway hyperresponsiveness have been reported. However, no significant differences were observed among the present CSA, CP and control groups with respect to age, sex or coronary risk factors, including smoking and allergic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Airway hyperresponsiveness is frequently encountered in patients with microvascular angina, 47 who experience breathlessness and anginal chest pain during physical or emotional stress with angiographically normal coronary arteries. The possibility that microvascular angina was included in the present CP group was not ruled out.…”
Section: Discussionmentioning
confidence: 99%